2016
DOI: 10.1007/s00296-016-3480-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-17 therapy in treatment of rheumatoid arthritis: a systematic literature review and meta-analysis of randomized controlled trials

Abstract: IL-17 has a role in inflammation in RA, and its levels in joints correlate with disease severity. Multiple RCTs have been performed to study effects of anti-IL-17 agents. The objective of this study was to perform a systematic review and meta-analysis to analyze the efficacy and safety of anti-IL-17 agents in the management of RA. This work is based on a systematic review of studies retrieved by a sensitive search strategy in PubMed, EMBASE and Cochrane CENTRAL from inception through 9/7/15. Study selection cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 34 publications
1
53
0
2
Order By: Relevance
“…Anti-TNF monoclonal antibodies are now the mainstay of rheumatoid arthritis treatment 160 and anti-IL-17 monoclonal antibodies have also shown some efficacy for the treatment of this disease 161 . Similarly, modulating IL-17 signalling, which is required for the development of lupus glomerulonephritis, with monoclonal antibodies is a potential therapeutic strategy for the treatment of SLE, especially in cases with kidney involvement 131 .…”
Section: Potential Therapeutic Modulation Of Netosismentioning
confidence: 99%
“…Anti-TNF monoclonal antibodies are now the mainstay of rheumatoid arthritis treatment 160 and anti-IL-17 monoclonal antibodies have also shown some efficacy for the treatment of this disease 161 . Similarly, modulating IL-17 signalling, which is required for the development of lupus glomerulonephritis, with monoclonal antibodies is a potential therapeutic strategy for the treatment of SLE, especially in cases with kidney involvement 131 .…”
Section: Potential Therapeutic Modulation Of Netosismentioning
confidence: 99%
“…In patients with RA, IL‐17 + FoxP3 + T cells can be identified in RA synovia and this provides further evidence of Treg/Th17 transdifferentiation . Although some clinical trials have not shown efficacy when using anti‐IL‐17 therapy for RA, there is evidence for increased Th17 cells following anti‐TNFα therapy . Moreover, evidence from phase two clinical trials with methotrexate, or in anti‐TNFα nonresponsive patients, indicates that disease in some RA patients is driven by Th17 cells and that treatment with anti‐IL‐17 antibody could be therapeutically beneficial (Table ) …”
Section: Th17 Cells and Rheumatoid Arthritis (Ra) Pathogenesismentioning
confidence: 99%
“…35 Although some clinical trials have not shown efficacy when using anti-IL-17 therapy for RA, there is evidence for increased Th17 cells following anti-TNFα therapy. 4,55,56 Moreover, evidence from phase two clinical trials with methotrexate, or in anti-TNFα nonresponsive patients, indicates that disease in some RA patients is driven by Th17 cells and that treatment with anti-IL-17 antibody could be therapeutically beneficial (Table 2). 57 RA is traditionally associated with the presence of rheumatoid factors and anticyclic citrullinated peptide autoantibodies.…”
Section: Arthritis (Ra) Pathogenesismentioning
confidence: 99%
“…Similarly, excessive IL-17 leads to the upregulation of neutrophil-attracting chemokines and subsequent neutrophil infiltration and inflammation during COPD 166, 167 . A number of biologic drugs targeting IL-17A/F and IL-17RA are being used or evaluated as treatment options against several diseases, such as COPD 168 , psoriasis, and RA, with impressive efficacy 169, 170 . However, IL-17 is strongly associated with the protection against Mtb clinical isolates and fungal infections.…”
Section: Anti-il-17 Therapies and Impact On Host Immunity To Infectionsmentioning
confidence: 99%